A study of correlation between Platelet Volume Indices (PVI) in patients of Dyslipidemia in tertiary care hospital - Dr. Alpesh M. Maru; Dr. Mayur JitubhaiKokani (Tropical Journal of Pathology and Microbiology, 2018)
Background:The dyslipidemia is a risk factors for cardiovascular disease. Ischemic heart disease istheleadingcauseofdeath worldwide. Platelet volume reflects platelet reactivity and has been suggested as an independent risk factor for ischemic events in cardiovascular disease. We have shown preliminary results on production of larger platelets by Mean Platelets Volume (MPV) and Platelets Distribution Width (PDW) determination in a group of patients with lipid profile abnormalities. Materials &Method:The study was performed in patients coming to GMERS Medical College, Junagadh from June 2016 to December 2017. Bloodsamplewascollectedinplaintubefor lipidprofileanalysis,EDTA vaccutainer for haematological analysis. PVI were obtained by usingHorriba 5 part automatedcellcounter & Lipid profile parameters by fully automated analyzer Roche’s COBAS INTEGRA 400plus. Results:our study comprising of 500 patient’s samples and 50 control samples, In patient’s group high levels of total cholesterol correlates more with high value of PDW than with MPV. Conclusion:PVI like MPV and PDW are strongly associated with dyslipidemia. The estimation of these PVI can be considered as an early, economicalandrapidprocedurefor identificationofcomplicationsinhyperlipidemic patients.